Optical soliton solutions of Schrodinger-Hirota equation with parabolic law nonlinearity via generalized Kudryashov algorithm - Cakicioglu, Hasan; Ozisik, Muslum; Secer, Aydin; Bayram, Mustafa (SPRINGER, 2023)
The aim of this study is to peruse the dispersive Schrodinger-Hirota equation (SH equation) with parabolic law linearity to get optical soliton solutions by utilizing the generalized Kudryashov method (GKM). Firstly, we introduced the solution algorithm of GKM. Then, we substituted the traveling wave transform to dispersive SH equation with parabolic law and gained nonlinear ordinary differential equation (NODE) form of real and imaginary parts. We successfully applied GKM to the NODE form of dispersive SH equation and obtained the appropriate solution sets. Using these sets, the solution of differential equation and necessary transformations, we created the analytical solution functions of dispersive SH equation and demonstrated the graphical simulations. Optical soliton solutions were obtained, graphical representations were made and interpreted, at the same time, it was observed that some parameters had an effect on the soliton behavior. The parabolic law form of the examined model has not been studied, and the obtained results have not been reported.
Keywords: Optical fibers; Generalized Kudryashov approach; Chromatic dispersion; The third order dispersion; DARK; PERTURBATION; Engineering; Physics; Optics